A 6-month pilot of a collaborative clinic between genitourinary medicine services and a young persons' sexual health clinic. Issue 2 (1st April 2003) - Beddard, Deborah; Chandiok, Swatantrata; James, Philippa; Russell, Antonia
Abstract : Objective: To investigate whether situating a genitourinary medicine (GUM) clinic within a Brook centre is successful in attracting a younger client group than that traditionally seen in GUM clinics within hospitals. Design: A descriptive study of a 6-month pilot clinic. Setting: Brook in Manchester. A community clinic providing sexual health advice to clients under the age of 25 years. With the collaboration of Withington Hospital GUM Department, Manchester. Participants: All clients under the age of 25 years attending the pilot GUM clinic. Main outcome measures: The age of the clients attending and the diagnosis made. Results: A total of 137 visits were made by 93 clients. Under-16s comprised 6% of all visits compared to 1.5% at Withington GUM clinic (adjusted for the under-25s) and 12% at Brook. Far more Chlamydia trachomatis was seen (34% of all clients) than in a traditional GUM clinic (18% of all clients). Contact tracing resulted in 82% of named contacts being traced. Conclusion: The pilot clinic was successful in attracting a much younger client group than a traditional hospital-based service.